2007
DOI: 10.1177/07419325070280060201
|View full text |Cite
|
Sign up to set email alerts
|

School Characteristics Related to High School Dropout Rates

Abstract: A B S T R A C T Dropping out of high school culminates a long-term process of disengagement from school and has profound social and economic consequences for students, their families, and their communities. Students who drop out of high school are more likely to be unemployed, to earn less than those who graduate, to be on public assistance, and to end up in prison. The present study examined dropout rates in Kentucky high schools ( N = 196), using both quantitative and qualitative procedures. Pearson product-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 9 publications
3
158
0
6
Order By: Relevance
“…Although SROs have been implemented to increase the safety of students and schools, there may be iatrogenic effects associated with their presence, including increased rates of exclusionary discipline (Hirschfield 2008;Kupchik 2010;Kupchik and Monahan 2006) that lead to negative impacts on students and schools (Balfanz et al 2015;Christle et al 2005Christle et al , 2007Perry and Morris 2014). The Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SROs have been implemented to increase the safety of students and schools, there may be iatrogenic effects associated with their presence, including increased rates of exclusionary discipline (Hirschfield 2008;Kupchik 2010;Kupchik and Monahan 2006) that lead to negative impacts on students and schools (Balfanz et al 2015;Christle et al 2005Christle et al , 2007Perry and Morris 2014). The Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of exclusionary discipline is also associated with poorer outcomes for schools more generally. Schools that use more exclusionary discipline fare worse on standardized tests (Raffaele Mendez et al 2002;Rausch et al 2004) and have higher dropout and lower graduation rates (Christle et al 2007). Highly punitive environments have negative academic consequences even for students who are not direct recipients of discipline (Perry and Morris 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that students (particularly boys) who perceive relationships with teachers as negative are at a significantly greater risk of dropping out (Lessard et al, 2004). Additionally, positive relationships with peers, the feeling of belonging, absence of peer violence, as well as participation in extracurricular activities and different kinds of dialogue in the classroom and school are related to lower incidence of dropping out of educational system (Christle, Jolivette & Nelson, 2007;Erktin, Okcabol & Ural, 2010;European Commission, 2015;Fortin et al, 2013;Pooley et al, 2008). Furthermore, it has been shown that strict measures for punishing students with disciplinary problems or poor attendance represent a significant factor connected to dropping out.…”
Section: Dropping Out Of Schoolmentioning
confidence: 99%
“…Having examined relevant reference works (Christle, Jolivette & Nelson, 2007;Erktin, Okcabol & Ural, 2010;Fortin et al, 2013;Lessard et al, 2004;Lyche, 2010;Pooley et al, 2008), we identified the areas of school life and work which can be associated with dropping out of educational system. Therefore, interview and focus group guidelines covered the following topics: (1) Physical conditions in school, (2) Teacher-student relationship and emotional 56 PSIHOLOŠKA ISTRAŽIVANJA VOL.…”
Section: Data Gathering and Analysis Techniquesmentioning
confidence: 99%
“…Academic motivation and achievement is also affected by perceived teacher support (Baeten et al (2013)), teacher attachment (Learner & Kruger (1997)) and the perceived classroom environment (Christle et al (2007)). A positive relationship has also been observed between school attachment/sense of belonging to school and academic motivation (Goodenow, 1993;Hagborg, 1998;Neel & Fuligni, 2013;Sánchez, Colón, & Esparza, 2005).…”
mentioning
confidence: 99%